A Review On TB And Its Advance Diagnostic Techniques - SWARNLATA PANCHAL; SHOBA KULSHESTRA; TK KHUBLANI (International Journal of Pharma and Bio Sciences, 2011)
In the Industrialized world, the times has gone when Laboratories need weeks to month to diagnose Tuberculosis from clinical specimens, Currently the Mycobaecteriology Laboratory is Experiencing more changes than ever before, Past decade, new methods for culture and susceptibility testing as well as molecular tools have been introduced which allow a rapid laboratory diagnosis of TB.so it is necessary to diagnose the disease with particular test prescribed by the specialist.